Q96195
Solution:
"d\/dx(f(x)+g(x))=f'(x)+g'(x)" -------(1)
And for a composite function f(g(x)), its's derivative is defined as:
"df\/dx=f'(g(x))*g'(x)" -----(2)
Moreover, "d\/dx(ln(x))=1\/x" -----(3)
Also, given:
"g(1)=1" ----(4)
"g'(1)= -9" ----(5)
"f'(0)=7" ----(6)
Now, "H(x)=f(ln(x))+ln(g(x))"
thus, using (1), (2) and (3),
"H'(x)=" "dH\/dx=f'(ln(x))\/x +g'(x)\/g(x)"
hence, "H'(1) = f'(ln(1))\/1 +g'(1)\/g(1)" (since, "ln(1) = 0" )
"=f'(0) + g'(1)\/g(1)"
"= 7 + (-9\/1)" (using (4), (5) and (6))
"= 7-9"
= -2 (Answer)
Comments
Leave a comment